Perbandingan Ketentuan Pidana Legislasi Nasional Negara Sponsor Deep-Seabed Mining - Ratna Galuh Manika Trisista; Farhana Farhana; Hamdan Azhar Siregar (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
National legislation is the requirement established by the International Seabed Authority (ISA) for each country sponsoring Deep-seabed Mining (DSM) and criminal provisions and sanctions are an inseparable part of it. A total of 38 states are listed as sponsoring states, while Indonesia, with its potential as a maritime country and member of UNCLOS 1982, has not participated in DSM activities. This article aims to explore and compare the criminal provisions in the national legislation of sponsoring states that have been approved by the ISA so that the formulation of sanctions in Indonesian national legislation can be illustrated in order to prepare Indonesia’s contribution as a sponsoring state for DSM activities in the International Seabed Area. The research method used is normative juridical with a statute and comparative approach. The research results show that the majority of sponsoring states in their criminal provisions stipulate criminal sanctions in the form of fines as well as the possibility of imprisonment and several administrative sanctions. Based on the results of this comparative study, it can be concluded that the formulation of sanctions that can be regulated in Indonesian national legislation is a maximum fine of more than 100 billion Rupiah and a maximum prison sentence of not less than 5 years, as well as additional criminal penalties and administrative sanctions in the form of termination or revocation of DSM activity permits, confiscation of profits resulting from illegal DSM acquisition, and compensation for environmental damage caused by DSM activities.